Literature on Trial : The Emergence of Critical Discourse in Germany, Poland & Russia, 1700-1800 - Chrostowska, S. D. (Sylwia Dominika), 1975- (Book collections on Project MUSE., 2012)
Analysing works by Lessing, Goethe, and Karamzin, among others, Literature on Trial brings a fresh theoretical perspective to the links between genre as a discursive strategy and socio-political life.